Codigestão anaeróbia de lixiviado de aterro sanitário e glicerol em reator de leito fixo visando o tratamento e a produção de biogás - Bottega, Lucas Decarli (2019)
Due to the National Solid Waste Policy (NSWP), established by Law no 12,305/2010, there is going to be a significant increase in the number of landfills in Brazil which, consequently, is going to lead to an increase in the volume of leachate generated, which must be properly treated. In addition, due to the National Program for the Production and Use of Biodiesel (NPPB), which set the percentage of biodiesel addition in common diesel at 10%, the supply of crude glycerol is going to increase, which needs to be properly allocated. Considering the necessity of studying and developing new alternatives for the use and treatment of these residues, the present study evaluated the anaerobic co-digestion of the landfill leachate and glycerol in a continuous upflow fixed-bed reactor at a mesophilic temperature of 37 oC and with medium support in high density polyethylene (HDPE), seeking removal of organic matter (COD) and biogas production. Different glycerol additions (0.24, 0.40, 0.80, and 1.20%) in volume and different Hydraulic Detention Times (HRT of 40, 64, 88, and 98 hours) were analyzed, which generated volumetric organic loads (VOL) with values between 1.93 and 5.23 gDQO.L-1reator.d-1, and accompanied by process stability indicators such as IA/PA and VA/TA. The COD removal results were satisfactory, ranging from 69.69 to 83.29%. As for the biogas production, results indicate values between 1.62 and 3.23 LN.day-1, with methane concentrations between 71.75 and 80.82%. A high concentration of ammonia nitrogen was also observed, above 1,600 mg.L-1, which, combined with the alkaline pH found, higher than 9.0 in three experimental conditions and close to this value in the other conditions, caused high concentrations of free ammonia in the reactor, above 1,000 mg.L-1. However, there was no evidence of inhibition of reactor activity due to such concentrations. Regarding the stability of the anaerobic co-digestion process, no signs of instability were found, since the IA/PA ratio remained below 0.20 in all experimental conditions and the highest value obtained for the VA/TA ratio was 0.05, thus indicating stability during operation, showing operational robustness. The capacity of the support medium was confirmed, in HDPE, to generate stability and keep the active biomass inside the reactor, minimizing the influence of the variations of the evaluated conditions’ characteristics. Moreover, the condition with the addition of 1.20% glycerol obtained the best result in terms of COD removal (83.29%) and had biogas production in the order of 3.23 LN.day-1, resulting in a methane production of 2.32 LNCH4.day-1, additionally to presenting volumetric reactor methane production of 0.9013 m3NCH4.m-3reator.day-1. Finally, it was found that the anaerobic codification of landfill leachate and glycerol in a fixed-bed reactor proved to be a robust and reliable process, which can be considered an interesting alternative for both waste treatment and energy recovery through production of clean energy.